Reduction of three-dimensional metal oxides for hydrogen regeneration using ultraviolet laser irradiation. (13th March 2019) - Seo, Keumyoung; Lim, Taekyung; Jeong, Sang-Mi; Ju, Sanghyun
Abstract: Hydrogen energy has been attracting much attention as a new clean energy source that can be infinitely supplied from water and living organisms. Among the various methods for generating hydrogen energy, CO2 -free thermochemical water splitting has recently been studied. This study reports a method capable of repeated hydrogen regeneration using metal oxide materials subjected to ultraviolet (UV) laser irradiation. The thermochemical water-splitting method, which produces hydrogen by the reaction of water vapor with a 3D microporous Ni structure having a large reaction surface area, was used to increase the efficiency of hydrogen generation. The amount of initially generated hydrogen was approximately 5.38 μ mol · min –1 · g –1 . During hydrogen generation, the reaction sites on the Ni surface decreased as Ni was oxidized to NiOx, and the amount of generated hydrogen decreased to approximately 0.7 μ mol · min –1 · g –1 at the end of 180 min NiOx was then reduced at room temperature by inducing nickel-oxygen bond cleavage at a low energy level using UV laser irradiation. The amount of regenerated hydrogen was the same as its initial amount (approximately 193 μ mol · g –1 ), implying 100% recovery. The proposed method shows potential as an effective means for hydrogen recycling, offering significantly reduced recycling times for hydrogen regeneration compared to conventional heat treatment reduction methods.